To solve the quadratic equation \( x^2 + 8x = 9 \) by completing the square, follow these steps:
-
Move the constant term to the other side of the equation:
\[ x^2 + 8x - 9 = 0 \]
-
Isolate the \( x \) terms:
\[ x^2 + 8x = 9 \]
-
Complete the square. Take half of the coefficient of \( x \) (which is 8), square it, and add it to both sides of the equation. Half of 8 is 4, and \( 4^2 = 16 \):
\[ x^2 + 8x + 16 = 9 + 16 \]
-
Simplifying gives:
\[ x^2 + 8x + 16 = 25 \]
-
The left side can be factored as a perfect square:
\[ (x + 4)^2 = 25 \]
-
Now take the square root of both sides:
\[ x + 4 = \pm 5 \]
-
This gives us two equations to solve for \( x \):
- \( x + 4 = 5 \)
- \( x + 4 = -5 \)
-
Solving these:
-
For \( x + 4 = 5 \): \[ x = 5 - 4 = 1 \]
-
For \( x + 4 = -5 \): \[ x = -5 - 4 = -9 \]
-
Thus, the two values that solve the quadratic equation \( x^2 + 8x = 9 \) are:
\[ x = 1 \quad \text{and} \quad x = -9 \]